Rapid identification of the authenticity of iron rod yam by in-situ mass spectrometry based on random forest algorithm - ZHONG Hengyan; CHEN Chun; OUYANG Yongzhong; ZHOU Lin; GUO Weiqing (Shipin yu jixie)
ObjectiveTo establish a fast and nondestructive analysis method for identifying iron rod yam.MethodsAtmospheric pressure chemical ionization mass spectrometry (APCI-MS) was employed to detect the chemical constituents of iron rod yam(TG) and non-iron rod yam (FTG) from different origins under ambient temperature and pressure, With 200 sets of data collected from each type of TG and FTG, and a total of 3 600 mass spectrometry data points were obtained. Subsequently, the initial level of the mass spectrometry data obtained was analyzed using Principal Component Analysis (PCA) and the random forest (RF) algorithm. Pattern recognition analysis established a model to differentiate between TG and FTG based on their chemical compositions.ResultsThe difference between the first-level mass spectra obtained by HS-APCI-MS was obvious between TG samples and FTG samples. The cumulative variance contribution plot of the principal components showed that the first seven principal components accounted for 85.63% (≥85%) of the variance. The accuracy of the training set and detection set reached 100% when the number of decision trees was 25. HS-APCI-MS combined with RF algorithm had a significant identification effect on TG, and the classification effect of RF was superior to that of PCA.ConclusionAtmospheric pressure chemical ionization mass spectrometry, combined with the RF algorithm, can rapidly and non-destructively identify TG and FTG, providing a new technical method for authenticating TG.